Multinational firms, labor market discrimination, and the capture of outsider's advantage by exploring the social divide - Siegel, Jordan; Pyun, Lynn; Cheon, B.Y. (Administrative Science Quarterly)
We theorize that foreign multinationals wield a particularly significant competitive weapon in host markets: as outsiders, they can pinpoint social schisms in host labor markets and exploit them for competitive advantage. Using two data sets from South Korea, we show that multinationals improve profitability and productivity by aggressively hiring an excluded group, women, in the local managerial labor market. We predict and find that foreign multinationals in South Korea are in a unique position to identify social schisms, implement practices designed to support and enhance the hiring and promotion of female managers, hire and promote members of the socially excluded group to positions of managerial leadership, and enjoy a net profitability benefit from doing so despite the real risk of backlash from some regulators, customers, suppliers, and employees from the socially dominant group in society. Many multinationals, even those whose home markets discriminate against women, appear to have recognized the strategic opportunity of what we call the outsider$1 (Bs network advantage. The gradualness of the host market$1 (Bs shift toward a new equilibrium freer of discrimination presented multinationals a multiyear competitive opportunity for outsider$1 (Bs advantage. Our study extends understanding of the multinational enterprise by showing how its competitive opportunities include identifying and exploiting social schisms in a host country$1 (Bs labor market. - Reproduced. s
Keywords: Labour market